2013
DOI: 10.1103/physrevb.87.144422
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen vacancy-mediated room-temperature ferromagnetism in insulating cobalt-substituted SrTiO3epitaxially integrated with silicon

Abstract: Room-temperature ferromagnetic insulating behavior is demonstrated in cobalt-substituted

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
40
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 51 publications
8
40
1
6
Order By: Relevance
“…This was confirmed by recent X-ray photoelectron spectroscopy measurements, where the Co 2p spectrum showed a peak at about 780.5 eV, accompanied by a strong shake up satellite feature at about 6.0 eV higher binding energy indicative of the high spin +2 valence state [1]. It is therefore imperative to consider the presence of additional carriers when describing the physics of this system.…”
Section: IVmentioning
confidence: 50%
See 4 more Smart Citations
“…This was confirmed by recent X-ray photoelectron spectroscopy measurements, where the Co 2p spectrum showed a peak at about 780.5 eV, accompanied by a strong shake up satellite feature at about 6.0 eV higher binding energy indicative of the high spin +2 valence state [1]. It is therefore imperative to consider the presence of additional carriers when describing the physics of this system.…”
Section: IVmentioning
confidence: 50%
“…Additionally, it was found that Co substitution induces an amount of oxygen to be removed from SrTiO 3 that is roughly the same as the Co concentration, which is much higher than the amount of oxygen vacancies proposed in [26]. It was also found in [1] that a robust ferromagnetic hysteresis loop was observed only at a sufficiently high Co concentration (~30%) and that samples exhibiting ferromagnetism were highly insulating, suggesting the absence of free carriers.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations